A Comparative Study on the Thermoelectric Properties of Bismuth Chalcogenide Alloys Synthesized through Mechanochemical Alloying and Microwave-Assisted Solution Synthesis Routes - Hamawandi, Bejan; Mansouri, Hamta; BALLIKAYA, Sedat; Demirci, Yunus; Orlovská, Martina; Bolghanabadi, Nafiseh; Sajjadi, Seyed A.; Toprak, Muhammet S. (Frontiers in Materials, 2020)
The way a material is synthesized and processed has an immense effect on its microstructure, which in turn has a big impact on its transport properties. Here we compare the thermoelectric (TE) properties of n- and p-type Bi2-xSbxTe3 (x: 0 and 1.5) materials synthesized through two different routes, specifically mechanochemical alloying (MA) -as a solid-state synthesis route, and microwave-assisted (MW) polyol synthesis -as a solution synthesis route. Reaction time is significantly reduced in the MW synthesis, leading to a significantly lower energy consumption (i.e. higher energy efficiency) per batch as compared to the MA route. The resultant materials are compared for their crystallinity, phase purity, morphology, and microstructure. Spark plasma sintering was used to prepare pellets and the resultant consolidates were evaluated for their transport properties. TE properties and microstructure of the specimens were investigated in relation to processing conditions and composition. MA samples formed fused structures (from 200 nm to several micrometers in size) composed of smaller particles. MW synthesized materials exhibit hexagonal platelet morphology, high crystallinity and phase purity. They also show lower thermal conductivity, leading to a higher resultant TE figure-of-merit -ZT. TE properties of Bi2-xSbxTe3 samples were studied on sintered cylindrical pellet samples, where the highest ZT values achieved were 1.04 (@ 440 K) for MW-Bi2Te3 and 0.76 (@ 523 K) for MW-Bi0.5Sb1.5Te3 samples, while MA-Bi2Te3 and MA-Bi0.5Sb1.5Te3 samples showed maximum ZT values of 0.74 (@ 460 K) and 0.27 (@ 300 K), respectively as n- and p-type TE materials. The observed trend is much higher ZT values for MW samples, ascribed to their higher degree of texturing and nanostructured grains reducing the thermal conductivity, thus achieving a better overall performance, verifying the prospect to enhance ZT using MW-assisted solution synthesis approach.